Mass Attenuation Coefficients of IAEA Soil Standards at Different Gamma-ray Energies - Shah, S. A.; Wasim, M. (The Nucleus, 2020)
Self-attenuation correction is very important in gamma-ray spectrometry of large samples. This paper presents the measurement of mass attenuation coefficients for three IAEA soil samples (IAEA-447, IAEA-TEL-2011-03, and IAEA-TEL-2012-03). It has been shown that the transmission method is important when the chemical composition of a sample is not known. For samples with established chemical composition, NIST offers WinXCom which provides mass attenuation coefficients based on the photon interaction data. WinXCom was applied and mass attenuation coefficients for the world average soil and IC-2018-01 soil were estimated. The mass attenuation coefficients required for the self-attenuation correction of soil samples for the determination of 226Ra, 232Th, 40K, and 137Cs have also been presented.